Highly efficient chemoselective N-tert butoxycarbonylation of aliphatic/aromatic/heterocyclic amines using diphenylglycoluril as organocatalyst. Issue 23 (5th June 2020) - Awasthi, Amardeep; Mukherjee, Anagh; Singh, Mandeep; Rathee, Garima; Vanka, Kumar; Chandra, Ramesh
Abstract: An efficient approach for the Chemoselective N- tert -butoxycarbonylation of a variety of amines using diphenylglycoluril as organocatalyst has been described. For the first time, a plausible mechanism for the N- tert -butoxycarbonylation has been proposed using density functional theory (DFT) calculations supported by NMR studies. The reusability of the organocatalyst and observation of the desired N-Boc protected amines being formed without the formation of side products like urea, oxazolidinone, isocyanate, and N, N-di-Boc derivatives makes the present protocol desirable. Graphical abstract: Image 1